The Mediating Impact of Value Chain in The Link Between Corporate Governance and SOE’s Performance - Dini Wahjoe Hapsari; Winwin Yadiati; Harry Suharman; Dini Rosdini (Australasian Accounting, Business and Finance Journal, 2023)
State-owned enterprises (SOEs) continue to improve their performance. One of the efforts taken by the Ministry of SOEs is to restructure the SOEs into holding companies based on clusters. The formation of each company cluster is carried out in stages. This study examines the effect of corporate governance, on the performance of SOEs with the mediating role of value chain. Corporate governance refers to the results of the corporate governance self-assessment, which is the uniqueness of the CG assessment for SOEs. Value chain analyzes all activities carried out by SOEs. Performance is measured comprehensively by combining financial and non-financial perspectives. Participants were general managers of the accounting and business process division in each state-owned enterprise. There are 138 participants. The results showed that corporate governance directly influenced value chain and SOE's performance, value chain affected SOE's performance. Value chain mediates the effect of corporate governance on SOE's performance.
Keywords: corporate governance; value chain; SOE’s performance